Crimination of food and beverage business persons that endanger health in consumer protection perspective - Gautama, Elly Christanti; Warka, Made; Prasetyawati, Endang; Setyorini, Erny Herlin (Technium Social Sciences Journal, 2021)
This research method uses normative legal research. The urgency of legal protection for food and beverage consumers from business actors that endanger health must receive attention from the community, local governments, government and other state institutions so that they can take responsibility for the health of every citizen. Every person or business actor, both stalls or street vendors who sell food and beverages that endanger the health and safety of the consumer's life, is essentially important to be monitored through the laws and regulations specifically stated in the Consumer Protection Act.